ENDOTELIAL-DEPENDENT OF THE REGULATION OF ANGIOGENESIS - Chertok, V M; Chertok, A G; Zenkina, V G (T͡S︡itologii͡a, 2017)
The review presents cellular and molecular mechanisms regulating angiogenesis. In response to the angiogenesis inducers impact the activated endothelial cells and their precursors (progenitor cells) synthesize and produce angiogenic molecule that differ by chemical origin and biological functions but all of them enable these cells to influence both directly and indirectly on new vessels growth. Among the great number of angiogenic molecules the scientists hold interests in the following: the set of vascular endothelial growth factors, the set of the fibroblast growth, transforming growth factor, tumor necrosis factor and some other soluble polypeptides which occurred to be an effective regulators of angiogenesis. However, despite the evident achievements in studies of cellular and molecular mechanisms of angiogenesis it is still difficult to control this process. Therefore the main goal of the study was to review endothelial-dependent factors and mechanisms of capillary vessels growth regulation.